Multiobjective Optimization of Port Collecting and Distributing Network Considering the Balance Among Efficiency, Environmental Performance, and Disruption to Urban Traffic - Yi Yang; Bochi Liu; Dongan Chen; Xinglu Xu; Wenyuan Wang (Journal of Advanced Transportation)
Port collecting and distributing network (PCDN) carries both freight traffic flow associated with the port and urban traffic flow, serving as the only channel between the port and the hinterland. The congestion caused by increasing freight traffic seriously disrupts urban traffic and leads to environmental issues such as increased carbon emissions. To address this issue, this study proposes a multiobjective optimization approach for the route selection of freight traffic flow within the PCDN, considering the balance among efficiency, environmental performance, and disruption to urban traffic. First, the generation mechanism and characteristics of freight traffic flow in the PCDN are analyzed, followed by the development of a mathematical model based on the static traffic flow distribution theory and the multiobjective optimization theory. Then, a solution framework with NSGA-III as the core is developed, and an improved Dial algorithm is utilized to allocate traffic flow. Finally, taking a large-scale container port as the case study, the solution framework is implemented to address the multiobjective optimization model and obtain the optimal route for freight traffic. The results show that there are significant negative correlations between distributing efficiency and disruption to urban traffic, as well as between distributing efficiency and carbon emissions. Decision-makers can choose the optimal route according to different preferences or adopt the compromise solution by referencing the Pareto front obtained by the solution framework. The proposed method provides theoretical support for designing the PCDN scientifically.